The Cambridge history of international law - Lesaffer, Randall; Peters, Anne (New York, New York : Cambridge University Press, 2024)
"Volume I introduces The Cambridge History of International Law series, offering a critical discussion of the development and current state of international law history writing across the world. Steering away from traditional Western historiography, this volume will interest scholars of international law across various disciplines"--
v. 1. The historiography of international law
Includes bibliographical references and index.
Keywords: International law; International law -- Political aspects; International law -- Economic aspects; International relations